Transposable 9T-SRAM computation-in-memory for on-chip learning with probability-based single-slope SAR hybrid ADC for edge devices - Jo, Yong-Jun (2023)
This letter proposes a two-way transposable SRAM computation-in-memory (CIM) macro for inference and training in convolutional neural networks (CNNs). A novel 9T SRAM bit-cell conducts local two-way computing without shared processing units, achieving higher-processing throughput from every bit-cell operating in one CIM cycle. This letter also proposes a probability-based single-slope (SS) and successive approximation (SAR) hybrid analog-to-digital converter (ADC) for energy efficiency improvement by utilizing the probability density function of multiply and accumulation (MAC). The proposed ADC also supports the ReLU-based zero skip function without additional circuitry. The prototype was fabricated in 180-nm CMOS technology and achieved an energy efficiency of 6.61 (1.65) TOPS/W for inference (training).